Asymmetric default bias in dishonesty – how defaults work but only when in one's favor - Toke R. Fosgaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
Based on a dice rolling task where participants can cheat on the outcome, this paper asks if default answers change dishonesty? The paper finds that various default answers have asymmetric effects. Compared to not having a default answer at all, providing a low default answer, or adding the expected mean as the default answer when participants report the outcome of the task do not affect behavior. Adding a high default answer, however, significantly increases the reported outcome.
Keywords: C91; D03; 330; Dice task; Cheating; Default bias